Pengaruh Media Pembelajaran Berbasis Augmented Reality terhadap Higher Order Thinking Skills (HOTS) Peserta Didik Sekolah Menengah Pertama - Dzulkifli; Eka Budhi Santosa; Fatma Sukmawati; Iqbal Ar Rasyid (Universitas Sebelas Maret, 2026)
The low level of Higher Order Thinking Skills (HOTS) among junior high school students in Indonesia, particularly in three-dimensional geometry, requires innovative instructional solutions. This study aims to investigate the effect of Augmented Reality (AR)-based learning media on the HOTS improvement of eighth-grade students in the topic of solid geometry at SMP Negeri 27 Surakarta. A quasi-experimental approach with a pretest-posttest control group design was employed. The sample consisted of 63 students (experimental group: n=31, control group: n=32) selected through purposive sampling. Data collection instruments were HOTS tests based on the revised Bloom's taxonomy (C4–C6), validated by experts. Data were analyzed using the Shapiro-Wilk normality test, Levene's homogeneity test, independent sample t-test, and N-Gain analysis. Results showed that the mean posttest score of the experimental group (75.11) was significantly higher than the control group (51.49). The independent sample t-test yielded a significance value of <0.001 (t = −11.348), leading to rejection of H₀. N-Gain analysis indicated an improvement of 60.31% (fairly effective category) in the experimental group versus 23.33% (ineffective category) in the control group. It is concluded that AR-based learning media significantly improves students' HOTS in solid geometry.